Using percentiles in the interpretation of Patient‐Reported Outcomes Measurement Information System scores: Guidelines for autism. Issue 12 (19th October 2022) - Schuchard, Julia; Kaplan‐Kahn, Elizabeth A.; Carle, Adam C.; Holmes, Laura Graham; Law, Kiely; Miller, Judith S.; Parish‐Morris, Julia; Forrest, Christopher B.
Abstract: The objectives of this study were to (1) demonstrate the application of percentiles to advance the interpretation of patient‐reported outcomes and (2) establish autism‐specific percentiles for four Patient‐Reported Outcomes Measurement Information System (PROMIS) measures. PROMIS measures were completed by parents of autistic children and adolescents ages 5–17 years as part of two studies ( n = 939 parents in the first study and n = 406 parents in the second study). Data from the first study were used to develop autism‐specific percentiles for PROMIS parent‐proxy sleep disturbance, sleep‐related impairment, fatigue, and anxiety. Previously established United States general population percentiles were applied to interpret PROMIS scores in both studies. Results of logistic regression models showed that parent‐reported material hardship was associated with scoring in the moderate–severe range (defined as ≥75th percentile in the general population) on all four PROMIS measures (odds ratios 1.7–2.2). In the second study, the percentage of children with severe scores (defined as ≥95th percentile in the general population) was 30% for anxiety, 25% for sleep disturbance, and 17% for sleep‐related impairment, indicating a high burden of these problems among autistic children. Few children had scores at or above the autism‐specific 95th percentile on these measures (3%–4%), indicating that their scores were similar to other autistic children. The general population and condition‐specific percentiles provide two complementary reference points to aid interpretation of PROMIS scores, including corresponding severity categories that are comparable across different PROMIS measures. Lay Summary: Patient‐reported outcome measures are used to assess patients' health from the perspective of patients and their families, but it can be difficult to interpret scores on these measures. This study demonstrated how percentiles may help clinicians and others understand patient‐reported outcome scores for children on the autism spectrum.